The Application of Capital Asset Pricing Model (CAPM) Analysis Method as the Basis of Stock Investment Decision Making: Study of 18 Technology Companies on the Indonesia Stock Exchange - Setya Negara, Ade Irma (HM Publisher, 2024)
This study aims to determine the application of the capital asset pricing model method as a basis for consideration in making stock investment decisions (study on shares of technology companies on the Indonesia Stock Exchange). The research variable is based on the concept of the Capital Asset Pricing Model. This research is a descriptive study with a quantitative approach. The population in this study is 27 shares of technology companies that have been listed on the Indonesia Stock Exchange (IDX) for the period November 2020-October 2022, while the sample is 18 company shares which is selected based on purposive sampling technique. The data processed is the closing price of shares (closing price) sourced from the IDX. The data was collected by literature study and data collection from several websites, including:(www.idx.co.id, www.finance.yahoo.com, https://www.bi.go.id and www.pefindo.com.) Data analysis is carried out by using the stages of the capital asset pricing model (CAPM) which starts from collecting stock closing price data to classifying stocks as investment decisions. The results of this study indicate that there is a unidirectional or non-linear relationship between systematic risk and the expected rate of return. There are 7 stocks that are included in the efficient stock category, and 11 stocks that are included in the inefficient stock category. Thus, the investment decision is to buy in efficient stocks and to sell in inefficient stocks if they have them.